A Schematic Review on Strategic Decision Making - R. Gopinathan (AG Volumes, 2021)
This research contrasts many theoretical models of the decision-making with how senior managers really make choices in the real world. As part of an investigation of the usage of decision-support technologies by notable decision-makers, we conducted interviews with a number of these individuals. Personal decision-making approaches were shown to be significantly different. The relevance of awareness to decision-making environment, attention towards the presentation of an information, including the use of the intuition emerged as major topics. Using an integrated approach for examining strategic choices, this literature review integrates the available research on contextual aspects. Strategic decision-making research tends to provide conflicting, inconsistent and inconclusive conclusions. Studies analysed show a wide range of impacts on strategic decision-making based on contextual factors. This opens up a slew of new avenues for further investigation. Cross-cultural studies, the longitudinal research, and evaluations of complicated linkages includes three-way interactions, the curvilinear connections, and the mediation effects were all underrepresented in the review. Conclusions include seven recommendations for further study and a slew of implications for theories and practises.